Peningkatan Motivasi Karir dan Kapasitas Pengusaha Mikro dalam Membangun Masa Depan yang Berkelanjutan di Desa Warnasari, Cileunca, Pangalengan: Pengabdian - Eti Jumiati; Yanthi Meitry Gunawan; Venny Oktaviany; Rezkiyana Hikmah; Damdam Damiyana (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The objective of this community service activity is to enhance career motivation and the capacity of micro-entrepreneurs in Warnasari Village, Cileunca, Pangalengan, so they can develop more sustainable and competitive businesses. The method used was training, which included interactive lectures, group discussions, and practical simulations on business planning, financial management, branding, and the use of technology in marketing. Evaluation was conducted using pre-tests and post-tests to measure changes in participants’ understanding. The results showed a significant increase in participants’ understanding of business management and planning, as well as the development of follow-up plans to grow their businesses. However, challenges remain, particularly limited capital and access to ongoing mentoring. The implication of this activity highlights the importance of long-term mentoring to support micro-entrepreneurs in applying the knowledge gained, and the need to expand access to capital and marketing to ensure sustainable business growth.